Lipid accumulation product, poverty income ratio, and bone mineral density in U.S. adults: a mediation analysis based on NHANES (2009–2020) - Chen, Zihao; Ye, Haobo; Li, Enli; Lin, Yuzhe; Jin, Chen; Yang, Lei (Frontiers in Nutrition, 2024)
Objective: This study aims to investigate the relationship between the lipid accumulation product (LAP) index and total femur bone mineral density (BMD), while also examining the mediating role of the poverty-income ratio (PIR). Methods: Using the most recent data from the National Health and Nutrition Examination Survey (NHANES) spanning 2009 to 2020, multivariate logistic regression models were employed in this study to investigate the relationship between the LAP index and total femur BMD. Saturation effects and potential non-linear associations were examined using a smooth curve-fitting approach to determine saturation levels. Interaction tests and subgroup analyses were also performed. Additionally, a mediation analysis was conducted to explore the mediating role of PIR. Results: 3,223 participants aged 20 years or older were recruited for this study. Multivariate regression analysis demonstrated a greater total femur BMD in individuals with a high LAP index. Additionally, analysis of the saturation effect and smooth curve fitting identified a clear saturation effect between the LAP index and total femur BMD. A saturation value of 16.05 was determined when investigating the relationship between the LAP index and total femur BMD. Subgroup analysis revealed no significant interaction effects after adjusting for covariates. Moreover, mediation analysis indicated that the LAP index had a substantial direct effect on total femur BMD (P < 0.0001), with PIR partially mediating this relationship (1.115%, P = 0.0280). Conclusion: The results of this investigation demonstrated a saturation effect between the LAP index and total femur BMD, which may have been mediated by PIR.